2020
DOI: 10.3389/fsurg.2020.582954
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Laparoscopic Management of an Ectopic Pregnancy in a Rudimentary Non-communicating Uterine Horn

Abstract: Introduction: Ectopic pregnancy in a non-communicating rudimentary uterine horn is a rare gynecological condition associated with a high risk of uterine rupture and important maternal mortality and morbidity. A surgical excision of the rudimentary horn is the standard treatment, usually performed by laparotomy in the second trimester. Methods: A 36-year-old woman, secundigravida and nulliparous, was admitted to the emergency obstetric unit with acute pelvic pain. The ultrasound found an ectopic pregnancy at 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…Finally, 72 reports were selected for our analysis. [ 7 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 ] Most of the articles were case reports, and we found 103 cases published from January 2000 to November 2020. Two reviewers (W.I.…”
Section: Ethodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, 72 reports were selected for our analysis. [ 7 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 ] Most of the articles were case reports, and we found 103 cases published from January 2000 to November 2020. Two reviewers (W.I.…”
Section: Ethodsmentioning
confidence: 99%
“…[ 5 10 ] To treat these cases, emergency laparotomy is performed. Apart from detecting hypovolemic shock,[ 11 12 13 14 15 16 17 ] patients frequently have abdominal pain,[ 7 11 13 14 15 16 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 ] but some reports have indicated that only 8% of rudimentary horn pregnancies (RHPs) are diagnosed before the symptoms appear. [ 44 ] Sufficient knowledge seems necessary to detect NCRHP during early obstetric screening.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Можливо ці заходи дозволити б своєчасно діагностувати локалізацію плідного яйця/плода та надати кваліфіковану допомогу лікарем акушер-гінекологом. Існують публікації про успішне неінвазивне виявлення вагітності у рудиментарному розі до його розриву та/або подальше хірургічне втручання навіть при появі «передвісників розриву» при стабільній гемодинаміці (Chatziioannidou et al, 2020, Bruand et al, 2020.…”
Section: обговоренняunclassified